1996
DOI: 10.3354/meps144133
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological response of the symbiotic sea anemone Aiptasia pallida to butyltin contamination

Abstract: This study investigates the fate of tributyltin (TBT), a widespread biocide mainly used in antifouling paints, and of its derivative dibutyltin (DBT) in sea anemones Aiptasia pallida exposed via water or food. Experiments were conducted on both symbiotic and aposymbiotic (lacking zooxanthellae) individuals under a 12 h light: 12 h dark photoperiod or in total darkness. TBT and DBT concentrations in the animal and vegetal compartments were measured over 24 h, 30 h, 5 d. 7 d and 28 d periods. Uptake and accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
(62 reference statements)
1
1
0
Order By: Relevance
“…Tentacle retraction and in other more extreme cases loss of tentacles (which was only observed in cAg NP) may have been due to a greater accumulation of NPs in the symbiont due to its greater tolerates [12]. This is reinforced by observations of retracted tentacles to tributyltin (a biocide in anti-fouling paint) in symbiotic anemones compared to no retraction of tentacles in aposymbiotic anemones [20] suggested that the host anemones are able to reverse translocate tributylin into the its symbionts, therefore, the loss of tentacles is likely to be a "last resort" mechanism, in which majority of the NPs are reverse translocated from the host to tissue into the symbiont (Figure 7). Furthermore, retracted or loss of tentacles also reduces its surface area.…”
Section: Behavioural and Microscopical Observationssupporting
confidence: 50%
“…Tentacle retraction and in other more extreme cases loss of tentacles (which was only observed in cAg NP) may have been due to a greater accumulation of NPs in the symbiont due to its greater tolerates [12]. This is reinforced by observations of retracted tentacles to tributyltin (a biocide in anti-fouling paint) in symbiotic anemones compared to no retraction of tentacles in aposymbiotic anemones [20] suggested that the host anemones are able to reverse translocate tributylin into the its symbionts, therefore, the loss of tentacles is likely to be a "last resort" mechanism, in which majority of the NPs are reverse translocated from the host to tissue into the symbiont (Figure 7). Furthermore, retracted or loss of tentacles also reduces its surface area.…”
Section: Behavioural and Microscopical Observationssupporting
confidence: 50%
“…Such properties of organotin compounds also render TBT an ecological risk to nontarget organisms exposed to TBT in aquatic environments, such as in harbors and areas that service boats ( ). Dissolved-phase concentrations of TBT less than 100 μg/L can cause growth and reproductive problems in mussels and oysters, and exposure to aquatic invertebrates is believed to cause endocrine disruption, such as imposex and intersex in gastropods ( , ).…”
Section: Introductionmentioning
confidence: 99%